Kajian Eksperimental Mesin Pendingin Adsorpsi Tenaga Surya dengan Menggunakan Adsorben Campuran - Sitorus, Tulus Burhanuddin (Jurnal Rekayasa Mesin, 2019)
The purpose of this study was to obtain the performance of the adsorption refrigerator driven by solar energy using mixed adsorbents. The refrigerant used is methanol with 99% purity. The adsorbent used is a mixture of active carbon-active alumina with mass of 7 kg. The type of active alumina used is molecular sieve 13X and the activated carbon used is the ordinary type of coconut shell with 1-3 mm grain size and is produced in the province of North Sumatra. Note that active alumina and activated carbon tested can absorb methanol in the range of 350 ml/kg and 300 ml/kg with a heat source of about 120oC. The test was carried out in the open field exposed to solar radiation from 08.00 WIB until 08.00 WIB the next day for seven cycles. The average of solar radiation ranges from 107.036-214.44 W/m2, and the duration of radiation varies from 12.03 to 12.28 hours/day during experiments. The test results also show that the use of mixed adsorbents with methanol adsorbate can produce evaporation temperatures up to about 4,16-13,90Â°C with a heat source from a temperature of 91.32-97.35Â°C. The efficiency of collector obtained during testing ranges from 60.09 to 62.26% with maximum solar radiation conditions ranging from 799.40 to 882.76 W/m2. The COP value obtained in the range 0.0770-0.1003 with the total daily radiation between 11.245-17.156 MJ/m2.